Die Anwendung der Elektrosortierung beim Recycling von Kunststoffen. Issue 6 (8th May 2014) - Reinsch, Edith; Frey, Andrea; Albrecht, Victoria; Simon, Frank; Peuker, Urs A.; Peuker, Urs
<x xml:space="preserve">Abstract</x> The continuous electric sorting is a process to separate mixed plastics in dry state with relatively little expenditure of energy. However, the electro‐static charging, which is the basic requirement for specific separation, is a physical phenomenon of high complexity. An overview is given of the state‐of‐the‐art of science about the electrostatic charging of plastics. Examples from practice are then employed to demonstrate to control of charging and separation processes.